Everyday life in besieged Sarajevo (1992–1995) - Szczesio, Sławomir Lucjan (City and War, 2021)
Sarajevo is the capital of Bosnia and Herzegovina, sometimes called the European Jerusalem. For many centuries, this city was a multi-ethnic society with a traditions of diversity and religious tolerance, between the East and West. Muslims, Serbs, Croats and other nationalities lived there peacefully, side by side. On the eve of war in 1992, about 50% of the city’s population was non-Muslim and many marriages were religiously and ethnically intermixed. After the referendum on independence of Bosnia and Herzegovina, the representatives of the three major nations of this republic couldn’t reach an agreement about the future. In April 1992, tensions in Bosnia and Herzegovina exploded into a bloody war. Sarajevo became a symbol of ethnic conflict and humanitarian intervention. The city was divided into two parts. A large part of Sarajevo, which was controlled by the government of Bosnia and Herzegovina, had been under siege by the Army of the Republika Srpska. During the three-and-a-half-year siege of Sarajevo, civilians were attacked by snipers and artillery shells in their homes, and while buying food in marketplaces, searching for water, and walking down the street. It was like Russian roulette. Food and water shortages had become a part of everyday life in Sarajevo. The supplies of electricity and gas were irregular. Airlifts and humanitarian relief (mainly from UNHCR) helped keep the city from starving. Despite months of siege, thousands of civilians dead, and the lives of each Sarajevan radically changed, the people of Sarajevo refused to yield to their aggressors.